Interpretasi dan Praktik Islam Berkemajuan pada Gerakan Muhammadiyah Cabang Limbung Kabupaten Gowa - Hadisaputra, Hadisaputra; Ismail, Lukman; Nur, Andi Asywid; Ikhsan, Fasikul (Sociology Department Of Syiah Kuala University, 2024)
This study examines the implementation of the concept of Islam Berkemajuan in the Muhammadiyah Branch of Limbung, Gowa Regency. The research uses a qualitative descriptive method with the social construction theory by Berger and Luckmann as the analytical framework. The study focuses on three main aspects: the organizations potential, the interpretation of Progressive Islam by leaders and members, and its implementation in organizational life and social contributions. Data were collected through observation and in-depth interviews. The results indicate that Muhammadiyah Limbung remains active in the Gowa Regency through various social enterprises in education, economy, and social sectors, supported by a solid organizational structure. The interpretation of Progressive Islam in Muhammadiyah Limbung is rooted in the values of the Qur'an and Sunnah, with an emphasis on moderation, openness, and community empowerment. The implementation of this concept is reflected in organizational strengthening, spiritual development, social enterprise growth, and social contributions through the framework of